Moral Consensus and Antiestablishment Politics - Johan Wennström (Research Institute of Industrial Economics (IFN), 2021)
This essay argues that mainstream Left and Right parties' convergence around the liberal moral foundations of care, fairness, and liberty most likely explains the popular discontent with establishment politicians and the ascendancy of insurgent political parties and movements in both Europe and the United States. It uses the moral consensus of two Swedish establishment parties, the Social Democratic Party and the right-wing Moderate Party, as its primary example. The convergence of those parties can be seen, for instance, in their approach to both education and immigration. The essay suggests that in order to win back wide public support, liberal Left and Right parties must become open to moral pluralism and acknowledge the legitimacy of conservative moral intuitions. Such pluralism would, in fact, be consistent with the traditions of liberalism.
Keywords: A13; D63; D70; D91; F60; J68; 330; Hedgehog-fox metaphor; Moderate Party; Moral foundations theory; Policy convergence; Social Democratic Party